2010
DOI: 10.1016/j.brainres.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Time of day differences in the number of cytokine-, neurotrophin- and NeuN-immunoreactive cells in the rat somatosensory or visual cortex

Abstract: Sensory input to different cortical areas differentially varies across the light-dark cycle and likely is responsible, in part, for activity-dependent changes in time-of-day differences in protein expression such as Fos In this study we investigate time-of-day differences between dark (just before light onset) and light (just before dark onset) for the number of immunoreactive (IR) neurons that stained for tumor necrosis factor alpha (TNFα), interleukin-1β (IL1β), nerve growth factor (NGF), the neuronal nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Hallett et al (2010) showed that individual whisker stimulation increased local expression of sleep regulating substances (nerve growth factor and interleukin-1 beta) in somatosensory cortex, providing support for the theory of local sleep. Hight et al (2010) showed circadian rhythmicity in sleep regulating substances in both somatosensory and visual cortex, providing support for the theory of local sleep. Krueger et al (2010) showed that purines and ATP affect sleep suggesting a basis for the local, homeostatic (use dependent) drive for sleep.…”
Section: Laboratory Studies In Animalssupporting
confidence: 55%
“…Hallett et al (2010) showed that individual whisker stimulation increased local expression of sleep regulating substances (nerve growth factor and interleukin-1 beta) in somatosensory cortex, providing support for the theory of local sleep. Hight et al (2010) showed circadian rhythmicity in sleep regulating substances in both somatosensory and visual cortex, providing support for the theory of local sleep. Krueger et al (2010) showed that purines and ATP affect sleep suggesting a basis for the local, homeostatic (use dependent) drive for sleep.…”
Section: Laboratory Studies In Animalssupporting
confidence: 55%
“…151,152 Recently, Hight et al found that the expression of NGF in somatosensory cortical neurons is high during the dark phase, while it is low during the light phase. 153 On the contrary, high levels of NGF are expressed in the visual cortex during the light phase, further supporting the modulation of NGF expression in brain pathways activated by light stimuli, and therefore that changes in circulating or brain NGF and BDNF levels might reflex the light/dark cycle. Remarkably, a daily fluctuation of NGF and BDNF in human serum and plasma, also related to sex, has been found in healthy subjects.…”
Section: Ngf and Bdnf As Neuromodulators Of Chronotherapeutics Of Depmentioning
confidence: 88%
“…The lack of response of IL-1 β to cocaine at light onset may be due to the fact that the high levels of IL-1 β mRNA at this time have reached their maximal levels. In response to activity during the night, IL-1 β -IR cells are greater in number at light onset than at dark onset [10]. At dark onset, the low dose of cocaine also significantly increased the number of IL1 β -IR astrocytes in the PFC, NAcc and somatosensory cortices, but not in the piriform cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, the central beta adrenergic receptors are involved in the activation of the cytokine, interleukin-1 β (IL1 β ), in the hypothalamus by methamphetamaine [7]. In the brain, cytokines act as sleep regulatory substances (SRSs) that are produced in response to neural activity [810]. Whisker stimulation increases the number of cytokine-IR cells in the somatosensory cortex.…”
Section: Introductionmentioning
confidence: 99%